Psychological Well-being as a Predictor of Celebrity Worship among College Students in Makassar - Humaidah, Ananda; Tetteng, Basti; Akmal, Nur (Universitas Negeri Makassar, 2023)
Abstrak. This study aimed at determining the effect of psychological well-being on celebrity worship among the college students who are fans of Korean dramas in Makassar City. The participants of this study were 402 students who were fans of Korean dramas in Makassar City. The sampling technique used was snowball sampling. The measurement tools used were Celebrity Attitude Scale to measure celebrity worship and Ryff's Psychological Well-Being Scale to measure psychological well-being. This study used a simple linear regression analysis technique. The finding was that there was an effect of psychological well-being on two aspects of celebrity worship, namely, intense personal feelings and pathological thresholds. Keywords: Celebrity worship, Psychological well-being